3(-8n-2)=-2n+16

Simple and best practice solution for 3(-8n-2)=-2n+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-8n-2)=-2n+16 equation:


Simplifying
3(-8n + -2) = -2n + 16

Reorder the terms:
3(-2 + -8n) = -2n + 16
(-2 * 3 + -8n * 3) = -2n + 16
(-6 + -24n) = -2n + 16

Reorder the terms:
-6 + -24n = 16 + -2n

Solving
-6 + -24n = 16 + -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
-6 + -24n + 2n = 16 + -2n + 2n

Combine like terms: -24n + 2n = -22n
-6 + -22n = 16 + -2n + 2n

Combine like terms: -2n + 2n = 0
-6 + -22n = 16 + 0
-6 + -22n = 16

Add '6' to each side of the equation.
-6 + 6 + -22n = 16 + 6

Combine like terms: -6 + 6 = 0
0 + -22n = 16 + 6
-22n = 16 + 6

Combine like terms: 16 + 6 = 22
-22n = 22

Divide each side by '-22'.
n = -1

Simplifying
n = -1

See similar equations:

| 24x-4x^2=0 | | 3y-9=6y+3 | | 5x+5(2+6x)=10+3x | | (6+y)(3y+7)=0 | | (2x)lnx+x=0 | | -15-5r=5(1+3r) | | (5v-7)(3-v)=0 | | 4x+4=5x+10 | | (2n-3)(n+4)=0 | | 6c-6-2c-5-3c+7= | | 8+(x+5)= | | x^3-10x^2+13x+74=0 | | 5b+3(3b+4)=-24+2b | | x*2-x=20 | | v=(50-2x)(50-2x)(x) | | y=5*cos*2x+11 | | (5z+6)(4-z)=0 | | q-1=5q+3q-8 | | 0.16=-0.4+0.7x | | 8.5+3.4= | | (4z+7)(5+z)=0 | | 1.2=-1.4+20x | | -9x+4y=7 | | 5x-y=14.9 | | 5x+7=-6+2x+19 | | 4x+y-4=0 | | 4x-9=-3x+5 | | 3(4x-2)+5x=30x | | S^2+2s= | | -4x-9=2x+9 | | 2=2.2x-15 | | 5-11p=17 |

Equations solver categories